EKSISTENSI KAJIAN AKADEMIK DALAM PEMBENTUKAN PERDA (STUDI PADA PEMBENTUKAN PERDA DI KABUAPTEN SOLOK SELATAN PERIODE 2004 – 2018) - Dendi Kurniawan; Deaf Wahyuni Ramadhani; Hendra Suherman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study tries to find out how the existence of Academic Papers in the Formation of Regional Regulations in South Solok Regency, the mechanisms for preparing Academic Papers in the formation of Regional Regulations in South Solok Regency and what obstacles were faced by the formation of Regional Regulations in the preparation of Academic Papers in South Solok Regency (Period 2004 -2018).The research was carried out using descriptive juridical-normative and juridical-empirical research methods using statutory approaches (statute approach) and conceptual approaches (conceptual approach).The results of the study show that the existence of Academic Papers for the formation of Regional Regulations in Solok Regency from 2004 until the end of 2013 was not preceded by an Academic Study even though the laws and regulations ordered to include Academic Papers in the formation of Regional Regulations.Since 2014 the paradigm of the South Solok Regency Government has begun to change.Since 2014 until now the formation of (new) Regional Regulations has always even been obliged to be accompanied by Academic Papers.This shows that the current condition of the Regional Government of South Solok Regency views the position of Academic Papers in the formation of Regional Regulations as having a very important position.The mechanism for preparing Academic Manuscripts carried out in Solok Selatan Regency is not entirely in accordance with the provisions of the laws and regulations.Especially if the Academic Paper is prepared independently by SOPD without involving third parties.The obstacles faced in the preparation of Academic Papers were Juridical Constraints, namely obstacles that came from the uncertainty of the formulation of laws and regulations, and non-juridical obstacles, namely: lack of data, harmonization of time and quality of human resources owned by the Regional Government of South Solok Regency.